The Rooster Bar - Grisham, John (New York : Doubleday, 2017)
Three students who have borrowed heavily to attend a third-rate law school realize they have been caught in a scam when they discover that the school's owner also owns a bank specializing in student loans, and plot to expose the scam.
Keywords: Student loans -- Fiction; Law schools -- Fiction; Legal fiction (Literature)